Chlorophyll a concentration of phytoplankton during a cruise of the 52nd Japanese Antarctic Research Expedition in 2010–2011 - TAKAHASHI, Kunio T.; TAKAMURA, Tomomi R.; ODATE, Tsuneo (2015)
P(論文) Fig. 1 | http://polaris.nipr.ac.jp/~parc/pub/v003/nipr_parc_175_0017.doc Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_175_0015.doc Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v002/nipr_parc_175_0016.doc departmental bulletin paper